EMU, Adjustment, and Exchange Rate Variability - Ricci, Luca.; Isard, Peter (Washington, D.C. : International Monetary Fund, 1998)
This paper uses a three-country, three-good, factor-specific model of trade with wage rigidities to investigate how European Monetary Union (EMU) is likely to affect exchange rate variability. Focusing on international macroeconomic adjustment under both exogenous and optimizing monetary policies, it shows that the relative variability (against external currencies) of the euro (under EMU) and a basket of present currencies (pre-EMU) depends on relative sizes and specialization patterns of EMU countries and the relative importance of different shocks. EMU is likely to decrease (increase) exchange rate variability for shocks to industries in which large (small) EMU countries are specialized.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet